PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN KEKERASAN DALAM PELAJARAN JARAK JAUH SELAMA MASA PANDEMI COVID-19 - Dhiya 'Ulhaq (2021)
This research discusses the spread of a disease called covid-19 so that it can interfere with daily activities, especially in the scope of schools and activities related to the gathering of many people, giving rise to a distance learning education system that causes high rates of violence to occur in children so that they can become victims. violence from people teaching and supervising them during distance learning. The formulation of the problem in this study is what are the factors that cause violence against children in distance learning during the covid -19 pandemic? What is the form of legal protection for children who are victims of violence in distance learning during the COVID-19 pandemic? In this study, the author uses a normative legal research method using a statutory approach and a case approach. The results of this study are, legal protection for children who are victims of violence in distance learning during the COVID-19 pandemic. The need for efforts to create education without violence.